Harnessing Simple Animal Models to Decode Sleep Mysteries - Pandi-Perumal, Seithikurippu R.; Saravanan, Konda Mani; Paul, Sayan; Chidambaram, Saravana Babu (Molecular biotechnology, 2024)
Whether it involves human subjects or non-human animals, basic, translational, or clinical sleep research poses significant ethical challenges for researchers and ethical committees alike. Sleep research greatly benefits from using diverse animal models, each offering unique insights into sleep control mechanisms. The fruit fly (Drosophila melanogaster) is a superior genetic model due to its quick generation period, large progenies, and rich genetic tools. Its well-characterized genome and ability to respond to hypnotics and stimulants make it an effective tool for studying sleep genetics and physiological foundations. The nematode (Caenorhabditis elegans) has a simpler neural organization and transparent body, allowing researchers to explore molecular underpinnings of sleep control. Vertebrate models, like zebrafish (Danio rerio), provide insights into circadian rhythm regulation, memory consolidation, and drug effects on sleep. Invertebrate models, like California sea hare (Aplysia californica) and Upside-down jellyfish (Cassiopea xamachana), have simpler nervous systems and behave similarly to humans, allowing for the examination of sleep principles without logistical and ethical challenges. Combining vertebrate and invertebrate animal models offers a comprehensive approach to studying sleep, improving our understanding of sleep regulation and potentially leading to new drug discovery processes for sleep disorders and related illnesses.